Regional Integration: Do Intra-African Trade and Migration Improve Income in Africa? - (:unkn) unknown (My University, 2020)
Regional integration in Africa is a subject of great interest, but its impact on income has not been studied sufficiently. Using cross-sectional and panel estimations, this article examines the impact of African integration on real per capita income in Africa. Accordingly, we consider intra-African trade and migration flows as quantitative measures reflecting the intensity of regional integration. To address the endogeneity concerns, we use a gravity-based, two-stage least-squares strategy. Our results show that, from a long-term perspective, African integration has not been strongenough to generate a positive, significant, and robust impact on real per capita income in Africa. However, it does appear to be significantly income-enhancing in the short and medium terms but only through intercountry migration. These results are robust to a wide range of specifications.
Keywords: African Research